JAPAN ’S IMMIGRATION POLICY : CLOSED FRONT DOOR AND PERFORMATIVE MIGRATION - Repečkaitė, Daiva (Politologija, 2015)
This paper analyses the official position of the Japanese government towards international labour migration to Japan, and the response from foreigners living in Japan – certain survival strategies, such as niche employment and performative migration. Although one of the electoral bases of the ruling Liberal Democratic Party – small businesses – push for more import of labour force, the ruling elite uses its institutional autonomy to resist their pressures and sustain the current restrictive stance. The official discourse of the government normalises only high- and middle-class labour migration, while the migration of the working class is notably viewed as abnormal and undeserved. Responding to this attitude, foreigners tend to either resort to ethnic networks for survival, or demonstrate their emotional relationship to Japan or commitment. Although Japan is peculiar with its restrictive stance towards the mobility of labour, the way migrant labour is conceptualised, sorted and channelled is in many ways similar to that of other states, although seemingly more “radical”. Thus, Japan presents an interesting case in developing theories of governmental responses to international labour migration.